2015
DOI: 10.1039/c5cp03171k
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier mobilities in organic semiconductors: crystal engineering and the importance of molecular contacts

Abstract: We have conducted a combined experimental and theoretical study on the optimization of hexa-peri-hexabenzocoronene (HBC) as organic semiconductor. While orientations with high electronic coupling are unfavorable in the native liquid crystalline phase of HBC, we enforced such orientations by applying external constraints. To this end, self-assembled monolayers (SAMs) were formed by a non-conventional preparation method on an Au-substrate using electrochemical control. Within these SAMs the HBC units are forced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…We use an unbiased quantum mechanics/molecular mechanics (QM/MM) scheme which was successfully applied to characterize CT in DNA, [22][23][24][25] in photolyases, cryptochromes [16][17][18] and also in organic materials. [26][27][28] We found a good agreement between the experimental values and our computational results for the classical tryptophan triad in the Escherichia coli CPD photolyase 16 or in the Arabidopsis thaliana plant cryptochrome: 17 we obtained rate constants differing by one order of magnitude or less from experimental data for forward charge transfer. Our QM/MM scheme allows the direct simulation of the charge motion along the different redox cofactors without any bias, which unravels the relative stability of the different redox states and the possible backward CT mechanisms (albeit the calculated backward rate constants are often overestimated).…”
Section: Introductionsupporting
confidence: 73%
“…We use an unbiased quantum mechanics/molecular mechanics (QM/MM) scheme which was successfully applied to characterize CT in DNA, [22][23][24][25] in photolyases, cryptochromes [16][17][18] and also in organic materials. [26][27][28] We found a good agreement between the experimental values and our computational results for the classical tryptophan triad in the Escherichia coli CPD photolyase 16 or in the Arabidopsis thaliana plant cryptochrome: 17 we obtained rate constants differing by one order of magnitude or less from experimental data for forward charge transfer. Our QM/MM scheme allows the direct simulation of the charge motion along the different redox cofactors without any bias, which unravels the relative stability of the different redox states and the possible backward CT mechanisms (albeit the calculated backward rate constants are often overestimated).…”
Section: Introductionsupporting
confidence: 73%
“…The presence of substantial contributions from lateral conductivity within self-assembled monolayers was further corroborated by Bashir et al through the application of molecular dynamics simulation where the charge transport was taken explicitly into account [29]. The theoretical study on the optimized model of HBC by using the Ehrenfest (mean field) approach demonstrated that the molecular packing of the monomers within the SAM is beneficial to the intermolecular electronic coupling and further promote charge carrier mobility.…”
Section: Resultsmentioning
confidence: 76%
“…To our knowledge, SPM methods have so far not been successfully used to determine the absolute thickness of organic self-assmbled monolayers, most likely due to difficulties with preparing a defined border between zones with and without the molecules on the substrate. Occasionally, using sophisticated patterning methods, height differences between two different SAMs have been determined [33]. Ellipsometry is suitable to measure thicknesses of monomolecular films, in principle, but the determination of crucial parameters like the complex refractive index of the SAM-forming molecule is not straightforward.…”
Section: Resultsmentioning
confidence: 99%